Blood Lead and High-Density Lipoprotein Concentrations in Relation to Human Blood Pressure: A Cross Sectional Study - Hu, Biao; He, Pei-yao; Zhong, Nan-nan; Gao, Zi-min; Guo, Jiang-long; Feng, Jun-tao; Huang, Chu-qin; Yang, Jun-bo; Sun, Dong-lin (Frontiers in Nutrition, 2022)
Background While the relationship between blood pressure and blood lead has been studied more extensively, the effect of high-density lipoprotein (HDL) concentration on this relationship remains uncertain. Therefore, this study aimed to determine the effect of HDL concentration on the relationship between blood lead and blood pressure. Methods The research used cross-sectional data from the 2005 to 2014 National Health and Nutrition Examination Survey (NHANES), which included 16,451 participants aged 20–60 years. Multivariable linear regression was used to evaluate the correlation among blood lead, systolic blood pressure (SBP), and diastolic blood pressure (DBP). HDL concentration was determined by low HDL concentration (≤ 49 mg/dl) and high HDL concentration (>49 mg/dl) stratified. The effect of HDL concentration was assessed by an interaction test between blood lead and SBP in multivariable linear regression. Results In this cross-sectional research, we identified a positive correlation between blood lead and SBP, but not DBP. The relationship between blood lead and SBP was different in the group with low and high HDL concentrations (β: 0.21 95% Cl:−0.05-0.46 vs. β:0.47 95% Cl: 0.15-0.79). In addition, high HDL significantly altered the positive correlation between blood lead and SBP (P-value of interaction < 0.001). Conclusion The study suggests an interaction between HDL and blood lead in elevating SBP, which may have important clinical implications.